Rubber (Hevea brasiliensis) seed meal: a potential material for livestock diets in Nigeria - Onuwaje O U
Rubber seeds were collected, dried, decorticated and milled, and the resultant rubber seed meal (RSM) was subjected to proximate analysis and to feeding trials as protein supplement in poultry pullet and layer ration.Defatted and defatted RSM were compared with regular commercial poultry mash purchased from the open market. Proximate analysis revealed that both defatted and defatted RSM contain acceptable levels of protein, crude fibre, solube minerals and vitamins. The amino acids-alanine, arginine, aspartic acid, glutamic acid, glycine, histidine, leucine, lysine, proline, serine, tryptophan and valine were present. Weight for weight, proline constitutes 0.02;while others were present in less than 0.001;. Weight gain and egg production per bird as well as the physical appearance of birds and eggs were identical for RSM and commercial feed. Percent (;)albumin, yolk, shell and egg weight were quantitatively similar for all feeds. Over a 10-week period average weight gains increased from 83.40gm to 1.83kg per bird for undefatted RSM. There is an indication that RSM is a worthy source of protein for livestock feeds; and industrial cum Institutional research cooperation is required to place RSM in the livestock feed market.
Keywords: Livestock diet; Nigeria; Rubber seed meal